Anchoring a plant cytochrome P450 via PsaM to the thylakoids in Synechococcus sp. PCC 7002: evidence for light-driven biosynthesis. - Lærke Münter Lassen (PLoS ONE, 2014)
Plants produce an immense variety of specialized metabolites, many of which are of high value as their bioactive properties make them useful as for instance pharmaceuticals. The compounds are often produced at low levels in the plant, and due to their complex structures, chemical synthesis may not be feasible. Here, we take advantage of the reducing equivalents generated in photosynthesis in developing an approach for producing plant bioactive natural compounds in a photosynthetic microorganism by functionally coupling a biosynthetic enzyme to photosystem I. This enables driving of the enzymatic reactions with electrons extracted from the photosynthetic electron transport chain. As a proof of concept, we have genetically fused the soluble catalytic domain of the cytochrome P450 CYP79A1, originating from the endoplasmic reticulum membranes of Sorghum bicolor, to a photosystem I subunit in the cyanobacterium Synechococcus sp. PCC 7002, thereby targeting it to the thylakoids. The engineered enzyme showed light-driven activity both in vivo and in vitro, demonstrating the possibility to achieve light-driven biosynthesis of high-value plant specialized metabolites in cyanobacteria.